2019
DOI: 10.3390/ijgi8020077
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Challenges on Entity Alignment of Geographic Knowledge Bases

Abstract: Geographic knowledge bases (GKBs) with multiple sources and forms are of obvious heterogeneity, which hinders the integration of geographic knowledge. Entity alignment provides an effective way to find correspondences of entities by measuring the multidimensional similarity between entities from different GKBs, thereby overcoming the semantic gap. Thus, many efforts have been made in this field. This paper initially proposes basic definitions and a general framework for the entity alignment of GKBs. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 123 publications
(165 reference statements)
0
23
0
Order By: Relevance
“…This is an advantage in terms of generality as the proposed method can be applied to various geospatial datasets. Moreover, an advanced method could be developed by combining various similarity measures, such as lexical similarity, structural similarity, category similarity, shape similarity, and so on [18,28,29] into the co-occurrence matrix, in which rows and columns represent entities under analysis, such as feature classes in this study. To combine these various similarity measures between these entities, it is necessary to determinate their weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an advantage in terms of generality as the proposed method can be applied to various geospatial datasets. Moreover, an advanced method could be developed by combining various similarity measures, such as lexical similarity, structural similarity, category similarity, shape similarity, and so on [18,28,29] into the co-occurrence matrix, in which rows and columns represent entities under analysis, such as feature classes in this study. To combine these various similarity measures between these entities, it is necessary to determinate their weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although the above studies showed good results, there is room for improvement by applying recent semantic analysis techniques [16][17][18] and developing new approaches to obtain hierarchical corresponding relations of feature classes between geospatial datasets, as well as within each dataset. These techniques begin from a co-occurrence matrix in which rows and columns represent individual entities used for analysis; in this study, feature classes are these entities.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, using the link information in the Wikipedia text (the correspondence between anchor text and entity) to make the word representation of entity in text as close as possible to the entity representation in knowledge bases, so as to realize the representation learning of text and knowledge base fusion; Zhong et al [29] also used similar ideas to fuse entity description information. Sun et al [30] summarized the current status of entity alignment algorithms in the field of geographical knowledge base research from three aspects of similarity measurement, similarity combination and consistency judgment, summarized the evaluation process of alignment results, and proposed the basic definition and general framework of entity alignment in a geographical knowledge graph. Guo et.al [31] proposed recurrent skipping networks for entity alignment (RSN4EA), which leverages biased RW (Radom Walk) sampling for generating long paths across knowledge graphs and generates the paths with a novel RSN (recurrent skipping network).…”
Section: Multi-knowledge Graph Fusionmentioning
confidence: 99%
“…Click the info button The review article of K. Sun, Y. Zhu and J. Song [15] describes the "Progress and Challenges on Entity Alignment of Geographic Knowledge Bases (GKBs)". To overcome the heterogeneity of GKBs, an entity alignment provides an effective way to find correspondencies of entities by measuring the multidimensional similarity between the entities from different GKBs.…”
Section: Hci and Gis In This Issuementioning
confidence: 99%